Discussion of solutions to ethical issues in real-world study - Wang, Sicheng; Liu, Baoyan; Xiong, Ningning; Xie, Qi; Zhang, Runshun; Zhou, Xuezhong; Qiao, Jie (Frontiers of medicine, 2014)
In recent years, the paradigm of real-world study (RWS) has been at the forefront of clinical research worldwide, particularly in the field of traditional Chinese medicine. In this paper, basic features and nature of real-world clinical studies are discussed, and ethical issues in different stages of RWS are raised and reviewed. Moreover, some preliminary solutions to these issues, such as protecting subjects during the process of RWS and performing ethical review, are presented based on recent practices and basic ethical rules to improve the scientific validity and ethical level of RWS.